Transformasi Dakwah Berbasis 'Kitab Kuning' Ke Platform Digital - Risdiana, Aris; Ramadhan, Reza Bakhtiar; Nawawi, Imam (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2020)
AbstractThe industrial revolution in digital era challanges Islamic Da'wah agencies. Its traditional method is originally exclusive, and that has been transformed into more inclusive. This paper studied activities of muslim leaders and mosques as the main actors of Islamic Da'wah (preachers), who contact with social medias. This study used sociological approach, to recover muslim preacher’s considerations of digital modalities as new media of Islmic preaching. Using Habitus theory of Pierre Felix Bourdieu, that study points out three main functions of social medias for muslim preachers; first. functioning social media requests the reinterpretation of Kitab Kuning in accordance with current social-political issues, second, Islamic preaching in digital era is kind of all capitalized activies, and third, muslim preachers polarized into three main groups; proactive, contrastive, and unprofessional.Keywords: Islamic Da’wah, Preacher, Social Media, Economy-political Interpretations.Revolusi Industri di era digital menantang para agen dakwah Islam. Metode dakwah Islam tradisional yang semula eksklusif, kini telah bertransformasi menjadi lebih inklusif. Penelitian ini mengkaji serangkaian aktivitas dakwah pemimpin Islam dan masjid, sebagai aktor utama dakwah Islam, yang bersentuhan dengan media sosial. Dengan pendekatan sosiologis, penelitian ini mengungkapkan kesadaran-kesadaran para da’i muslim tentang dunia digital sebagai media baru dakwah Islam. Menggunakan teori Habitus dari Pierre Felix Bourdieu, penelitian ini menemukan tiga hal utama; pertama, pemanfaatan media sosial menuntut interpretasi ulang kitab kuning agar lebih sesuai dengan perkembangan mutakhir isu-isu sosial-politik; kedua, dakwah Islam di era digital tidak lebih dari sekedar serangkaian aktivitas yang terkapitalisasi; dan ketiga para da’i muslim terpolarisasi ke dalam tiga kelompok utama: pro-aktif dengan media sosial, bersikap kontra produktif terhadap media, dan pro-media digital dalam kadar yang tidak profesional.Kata Kunci: Da’wah Islam, Da’i, Media Sosial, Tafsir Ekonomi Politik